Peningkatan Literasi Keuangan Untuk Memperkuat Wirausaha Pekerja Migran Malaysia - Kusbandiyah, Ani; Wahyuni, Sri; Tubastuvi, Naelati; Wati, Ratna Kartika; Fitriati, Azmi; Rahmah, Nunung Aini (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2024)
The aim of this Community Service is to increase insight and competence in the field of accounting, especially in understanding simple recording for Micro, Small and Medium Enterprises (MSMEs) in the Malaysian migrant worker environment. The level of knowledge of Financial Literacy among Micro, Small and Medium Business Actors among business actors in the migrant worker environment is generally still relatively low. One indicator that stands out is that most MSMEs owned by Malaysian migrant workers are trapped in online loans. The main problem faced by MSMEs is their low financial administration skills. The indicator can be seen from the fact that personal and business finances are still mixed up, so that it cannot be distinguished between the amount of assets owned, how much the bills are and how to prepare simple financial reports to obtain funding from the bank. As for the solution to overcome this problem, the IBM Faculty of Economics and Business Team will provide training and mentoring and introduce simple financial reporting technology using the Android application, which is an application that can be operated by MSME players offline, so that the financial administration system is more organized and biased. presented to obtain third party funding, (Banks and Investors).